The risky steady state and the interest rate lower bound - Timothy Hills; Taisuke Nakata; Sebastian Schmidt (European Central Bank (ECB), 2016)
Even when the policy rate is not at the effective lower bound (ELB), the possibility that the policy rate will become constrained by the ELB in the future lowers today's inflation by creating tail risk in future inflation and thus reducing expected inflation. In an empirically rich model calibrated to match key features of the U.S. economy, we find that the tail risk induced by the ELB causes inflation to undershoot the target rate of 2 percent by as much as 45 basis points at the economy's risky steady state. Our model suggests that achieving the inflation target may be more difficult now than before the Great Recession, if the recent ELB experience has led households and firms to revise up their estimate of the ELB frequency.
Keywords: E32; E52; 330; liquidity trap; zero lower bound